Beginner Functional Equation

Algebra Level 2

A function f : R + R f \colon \mathbb{R}^+ \to \mathbb{R} satisfies f ( x + y ) = f ( x ) f ( y ) f(x+y)=f(x)f(y) for all positive real numbers x x and y . y. If f ( 2 ) = 3 , f(2)=3, then find f ( 6 ) . f(6).


The answer is 27.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Suneel Kumar
Nov 30, 2015

Simply we can solve in the following way: f(6)=f(2+4)=f(2)f(4) =f(2)f(2+2) =f(2)f(2)f(2) =3.3.3=27 Hence f(6) = 27

First note that 3 = f ( 2 ) = f ( 1 + 1 ) = f ( 1 ) f ( 1 ) = f ( 1 ) 2 f ( 1 ) = ± 3 . 3 = f(2) = f(1 + 1) = f(1)*f(1) = f(1)^{2} \Longrightarrow f(1) = \pm \sqrt{3}.

Then f ( 3 ) = f ( 2 + 1 ) = f ( 2 ) f ( 1 ) = ± 3 3 , f(3) = f(2 + 1) = f(2)*f(1) = \pm 3\sqrt{3}, and so f ( 6 ) = f ( 3 + 3 ) = f ( 3 ) 2 = ( ± 3 3 ) 2 = 27 . f(6) = f(3 + 3) = f(3)^{2} = (\pm3\sqrt{3})^{2} = \boxed{27}.

Alternatively, we have that

f ( 4 ) = f ( 2 + 2 ) = f ( 2 ) f ( 2 ) = 3 3 = 9 f ( 6 ) = f ( 4 + 2 ) = f ( 4 ) f ( 2 ) = 9 3 = 27 . f(4) = f(2 + 2) = f(2)*f(2) = 3*3 = 9 \Longrightarrow f(6) = f(4 + 2) = f(4)*f(2) = 9*3 = \boxed{27}.

Kay Xspre
Nov 22, 2015

You can also derive a general term that, for an even number x x , the function f ( x ) f(x) may be written in the form of f ( x ) = ( 3 ) x f(x) = (\sqrt{3})^x

Y NOT "-root(3)^x" ???

Ganesh Ayyappan - 5 years, 6 months ago

Log in to reply

If x x is given even, ( 3 ) x = ( 3 ) x (\sqrt 3)^x=(-\sqrt 3)^x

展豪 張 - 5 years, 6 months ago
Andrew Yates
Dec 2, 2015

f(a+b+c)=f(a)f(b)f(c)

f(6)=f(2+2+2)=f(2)f(2)f(2)=3^3=27

If f(2) = 3, then f(2+2) = 3 * 3 = 9. Now, f(6) = f( 2 + 2 + 2 ) = f(2) * f(2 + 2) = 3 * 9 = 27.

nice way to solve

Sandeep Kumar - 5 years, 6 months ago
Rakesh Ranjan
Aug 16, 2016

One another solution:

f(6) = f(3+3) =2 f(3);;
f(3)=f(2+1)=f(2)f(1)=3
f(1);;
f(2)=f(1+1)=2*f(1)=3;;
f(1)=3/2;;


f(6)=2 (3 (3/2))=9

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...